Integrating Problem-Based Learning and Design Thinking for Sustainability: A Practical Approach to Teaching Real-World Problem Solving in Undergraduate Education - Hanji, Sanjay; Yempally, Veeranna; Baligar, Preethi; Jana, Krishnendu; Gautam, Avinita; Joshi, Gopalkrishna (Proceedings from the International Research Symposium on Problem-Based Learning (IRSPBL), 2025)
This practice paper presents the development, implementation and evaluation of a course, Design Thinking for Sustainability, a university core course for first-year students from undergraduate programs in Technology, Business administration, Computer applications and Design. As a greenfield private university in India, we integrated Design Thinking into the core curriculum to enhance problem-solving abilities. The course addressed real-world, ill-defined challenges through the United Nations' 17 Sustainable Development Goals (SDGs), equipping students with practical, creative problem-solving skills. Offered as a 21-day pre-semester credit course, it fostered interdisciplinary collaboration on sustainability-driven challenges. Using Problem-Based Learning (PBL) approach, students worked in teams, applying the five stages of Design Thinking—Empathize, Define, Ideate, Prototype, and Test—to develop innovative, sustainable solutions. The design thinking process encouraged iteration, collective work, and optional participation. With this first version of the course, the focus of evaluation was to explore the challenges faced by faculty members and students, which allow for revision during the next iteration of the course. The findings bring out various challenges perceived by our students and faculty members, and various strategies to overcome them. The challenges stated were psychological readiness for open ended problem-solving, struggle to identify and define real world problems, lacked access to stakeholders and sustainability related data. However, collaborative teamwork, prototyping and stakeholder feedback helped them to overcome the challenges and come up with feasible and workable solutions to the problems thereby developing problem solving skills. Faculty stated that they did not know design thinking whereas they learned it while during the course. Secondly, they had to put significant effort in designing, teaching and assessing in a way to promote active learning. They were agile during the course and did minor adjustments to the course during the course delivery. Overall, this paper provides practical insights for educators who will be seeking to integrate PBL and Design Thinking into their curricula, particularly with inclusion of sustainability-driven innovation and active learning.